2005
DOI: 10.1111/j.1467-8683.2005.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Executive Compensation Policy and Company Performance in Japan

Abstract: The purpose of this paper is to analyse whether companies'"way to pay their director" matters or not. Firstly, we fail to find a positive relationship between the performance-pay sensitivity and company performance. Thus, these results do not support our hypothesis that those companies that intensify the performance-pay sensitivity are more likely to improve their performance. In addition, this research fails to find a positive relationship between the change of pay policy and performance. These results are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 18 publications
1
46
2
1
Order By: Relevance
“…Previous studies are inconclusive in showing the influence of management pay incentives on firm performance. Some studies have found a relationship (Cordeiro et al, 2000;Dalton et al, 2003;Ryan & Wiggins, 2004), whereas others have not (Kubo, 2005;Vafeas, 1999). As in other variables, previous research results seem contradictory.…”
Section: Independence Of Board Members and Performancecontrasting
confidence: 43%
“…Previous studies are inconclusive in showing the influence of management pay incentives on firm performance. Some studies have found a relationship (Cordeiro et al, 2000;Dalton et al, 2003;Ryan & Wiggins, 2004), whereas others have not (Kubo, 2005;Vafeas, 1999). As in other variables, previous research results seem contradictory.…”
Section: Independence Of Board Members and Performancecontrasting
confidence: 43%
“…Japanese firms, at least for a large part of the postwar period, arguably sought non-financial goals, such as market share or employment, rather than financial objectives, such as profits or shareholder value (Aoki 1990;Porter 1990;Abegglen & Stalk 1985;Tsuru 1996;Geringer et al 1999;Ahmadjian & Robbins 2005;Kubo 2005; and others); though others dissent (e.g. Shivdasani 1995, 1997).…”
Section: Sales and Employment Growthmentioning
confidence: 99%
“…Comparative research has stressed the weaker effects of equity-based incentives in the UK and Germany (Bruce et al, 2005) or the absence of a link between high pay for performance sensitivity in executive pay and financial performance in Japan (Kubo, 2005). Crossnationally comparative research has therefore also further sensitized researchers to how different sets of institutions modify the basic principal-agent relationship by providing different sets of incentives, resources, and understandings of corporate governance.…”
Section: From the Principal-agency Dichotomy Towards A Comparative Inmentioning
confidence: 99%